Peran Rasa Kesepian dan Harapan dalam Memprediksi Kecenderungan Depresi pada Mahasiswa - Hidayati, Hidayati; Poerwandari, Elizabeth Kristi (Jurnal Online Psikogenesis, 2024)
This study aims to examine the model of positive constructs, hope and negative constructs, loneliness, in predicting depression tendencies among university students. Depression tendencies are a frequently encountered phenomenon. University students are in a transitional phase between adolescence and adulthood, a stage that can be quite confusing as they begin striving for independence yet are not fully independent. Academic demands, low social skills, and living apart from parents often lead to feelings of loneliness. Meanwhile, the presence of hope in individuals makes them more resilient in facing difficulties and striving to achieve goals, thus acting as a protective factor against depression. The study's participants consisted of 410 active undergraduate students from Jakarta, Bogor, Depok, Tangerang, and Bekasi. Statistical analysis using multiple regression showed that the model aligns with the assumptions, where loneliness predicts the presence of depression, and hope significantly serves as a protective factor against the emergence of depression (R²=0.456; F(6,409) = 58.183; p<.05).